Respiratory function rehabilitation in individuals with Covid-19: swimming exercise - Harun Genç; Ebru Ceviz; Oktay Kızar; Kadriye Dinçer (Physical Education of Students)
Background and Study Aim. Understanding the impact of swimming exercises on post-Covid-19 respiratory function is crucial for optimizing recovery strategies in affected individuals. The aim of this study is to determine the effect of 8-week swimming exercises on respiratory function parameters in adult individuals who have had Covid-19 disease.